Artistic Interpretation and Transformatsion of the Image of Historical Figures in Literature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the literary interpretation of three prominent historical figures - Amir Temur, Alisher Navoi, and Zahiriddin Babur - in Eastern, Russian, and Western literature. It explores how literary portraits are formed in works of different eras and cultures: Temur appears as a powerful ruler, strategist, and a symbol of strength and state unity; Navoi - as a prominent poet, reformer of Turkic poetry, and philosopher-humanist; Babur is a conqueror, poet, and exile who united the traditions of Central Asia and India. The purpose of this research is to identify the peculiarities of the literary interpretation of these historical figures in literature of different traditions and to analyze how historical memory influences the formation of cultural identity. The research objectives include: analyzing primary sources, including the works of historical figures themselves (“Baburnama”, “Khamsa”); studying classical and contemporary artistic works where their images are present; comparing literary interpretations in various cultural contexts; identifying key motives and changes in the perception of these figures over time. The research was conducted using methods such as comparative analysis, historical-literary method, and intertextual approach. As a result of the research, the peculiarities of the literary image of Amir Temur, Navoi, and Babur in the literary traditions of different peoples were revealed, and the influence of national and cultural factors on their interpretation was shown. In conclusion, it is emphasized that studying these images contributes to understanding the processes of historical memory and cultural identity formation in various societies.